2004
DOI: 10.1097/01.tp.0000131662.01491.2e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inhibition of Poly(Adenosine Diphosphate-Ribose) Synthase on Acute Cardiac Allograft Rejection

Abstract: The data indicate that PARS activation occurs during acute cardiac-allograft rejection and contributes significantly to the inflammatory response and to the death of cardiac muscle cells by apoptosis. They suggest that PARS inhibition combined with immunosuppression might enhance salvage of heart-muscle cells during acute cardiac-allograft rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…The observation that 5-aminoisoquinoline, an inhibitor of PARP, attenuated rejection scores and improved graft survival in a rodent model of cardiac allograft rejection suggests the importance of PARP activation (Liu et al, 2004). In our study, we found that WW85 given alone decreased poly(ADP-ribose), suggesting that it acted, in part, by decreasing PARP activation.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…The observation that 5-aminoisoquinoline, an inhibitor of PARP, attenuated rejection scores and improved graft survival in a rodent model of cardiac allograft rejection suggests the importance of PARP activation (Liu et al, 2004). In our study, we found that WW85 given alone decreased poly(ADP-ribose), suggesting that it acted, in part, by decreasing PARP activation.…”
supporting
confidence: 54%
“…PARP activation has been shown after reperfusion injury in rat cardiac transplants or following alloimmune activation and rejection in rat tracheal (Farivar et al, 2004) and cardiac (Liu et al, 2004) allografts. The observation that 5-aminoisoquinoline, an inhibitor of PARP, attenuated rejection scores and improved graft survival in a rodent model of cardiac allograft rejection suggests the importance of PARP activation (Liu et al, 2004).…”
mentioning
confidence: 99%
“…The cardiac protective effect of PARP inhibitors was subsequently extended into various models of heart transplantation. Treatment of the recipients with PARP inhibitors resulted in improved myocardial contractility and longer survival time of the transplanted hearts (Fiorillo et al, 2002(Fiorillo et al, , 2003Szabó et al, 2002Szabó et al, , 2005Szabó et al, , 2006Liu et al, 2004;Gao et al, 2007). The mode of action of PARP inhibitors, as cardioprotective agents, appears to involve a combination of mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic interventions that are shown to decrease nitrotyrosine formation in cardiac myocytes per se have, in general, also been shown to increase graft survival or inhibit histological rejection [52,129,130]. In studies using a COX-2 inhibitor, graft survival was prolonged with weak staining for nitrotyrosine which was confined to inflammatory cells [129].…”
Section: Cell Localization Of Nitrationmentioning
confidence: 99%